2015
DOI: 10.1021/acsnano.5b04552
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism of Chiral Nematic Films of Cellulose Nanocrystals Loaded with Plasmonic Nanoparticles

Abstract: In the search for induced chiral plasmonic activity, cholesteric films formed by cellulose nanocrystals have attracted great interest as potential hosts for plasmonic nanoparticles. Circular dichroism (CD) spectra of the composite films exhibit two peaks, one of which is ascribed to the cholesteric host and the other one to plasmonic chiroptical activity of the plasmonic nanoparticles. Here we report the results of comprehensive studies of extinction and CD properties of composite films formed by different typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
94
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(95 citation statements)
references
References 53 publications
1
94
0
Order By: Relevance
“…Second, helically twisted layer‐by‐layer structures have been generated by photolithographic techniques, in which each layer is composed of a periodic array of plasmonic nanoparticles (NPs) . Third, plasmonic NPs have been helically assembled on helical templates (such as DNA, peptides, chiral mesoporous silica, inorganic nanohelices, organic spiral fibers, and chiral nematic films of cellulose nanocrystals). Fourth, plasmonic helices have been generated without chiral ligands or helical templates, by means of direct laser writing into a positive‐tone photoresist followed by electrochemical deposition of gold, radio‐frequency plasma prior to electroless plating, multibeam holographic lithography, colloidal nanohole lithography, focused ion beam‐induced deposition, electron beam‐induced deposition, and glancing angle deposition (GLAD) .…”
Section: Introductionmentioning
confidence: 99%
“…Second, helically twisted layer‐by‐layer structures have been generated by photolithographic techniques, in which each layer is composed of a periodic array of plasmonic nanoparticles (NPs) . Third, plasmonic NPs have been helically assembled on helical templates (such as DNA, peptides, chiral mesoporous silica, inorganic nanohelices, organic spiral fibers, and chiral nematic films of cellulose nanocrystals). Fourth, plasmonic helices have been generated without chiral ligands or helical templates, by means of direct laser writing into a positive‐tone photoresist followed by electrochemical deposition of gold, radio‐frequency plasma prior to electroless plating, multibeam holographic lithography, colloidal nanohole lithography, focused ion beam‐induced deposition, electron beam‐induced deposition, and glancing angle deposition (GLAD) .…”
Section: Introductionmentioning
confidence: 99%
“…The hybrid system can potentially couple the chiroptical properties of the host matrix with the intrinsic optical properties of the NPs, leading to distinct plasmon‐induced chirooptical properties. Kumacheva and colleagues developed Au NPs‐CNC composite films with long range chiral ordering that showed strong optical activity depending on the Au NPs/CNC ratio, the size and shape of the Au NPs, and the helical pitch of the CNC . They confirmed that the composite film had chiral nematic phase and Au NPs were incorporated in the host CNC matrix, through polarized optical microscopy (POM) and SEM analysis.…”
Section: Macromolecule‐assisted Chiral Assembly Of Nanoparticlesmentioning
confidence: 99%
“…[ 20 ] In particular, these chiral liquid crystalline phases can serve as host to lodge non‐chiral guests such as nanoparticles and dyes. [ 21–23 ] The hybrid system can combine the chiroptical response of the matrix with intrinsic optical properties of the guests. [ 24,25 ] So far, chiral nematic liquid crystals formed by CNCs have been remarkably successful.…”
Section: Introductionmentioning
confidence: 99%